2008
DOI: 10.3748/wjg.14.4332
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of prednisolone on ischemia-induced liver injury in rats

Abstract: AIM:To investigate the effects of prednisolone on cell membrane bleb formation, calpain μ activation and talin degradation during hepatic ischemia-reperfusion injury in rats. METHODS:The hilar area of the left lateral and median lobes of rat liver (68%) was clamped for 60 min and followed by 120 min reperfusion. Prednisolone was administered at 1.0, 3.0, or 10 mg/kg at 30 min before ischemia. In addition to biochemical and microscopic analyses, activation of calpain μ was determined using specific antibodies a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 20 publications
1
9
1
Order By: Relevance
“…Interestingly, our results reveal that administration of a relatively low dose of methylprednisolone (5 mg/kg, corresponding ~0.8 mg/kg in humans [19]) exacerbates the CMV-induced diaphragm dysfunction, whereas a higher dose (30 mg/kg, corresponding ~5 mg/kg in humans [19]) completely protected the diaphragm against VIDD. The dose-depending effect of corticosteroids are in agreement with previous studies [7,8,31]. Our finding of a negative correlation between calpain activity and either diaphragmatic force production or diaphragm fiber CSA further supports the notion that calpain activation plays an important role in CMV-induced diaphragmatic atrophy and contractile dysfunction.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, our results reveal that administration of a relatively low dose of methylprednisolone (5 mg/kg, corresponding ~0.8 mg/kg in humans [19]) exacerbates the CMV-induced diaphragm dysfunction, whereas a higher dose (30 mg/kg, corresponding ~5 mg/kg in humans [19]) completely protected the diaphragm against VIDD. The dose-depending effect of corticosteroids are in agreement with previous studies [7,8,31]. Our finding of a negative correlation between calpain activity and either diaphragmatic force production or diaphragm fiber CSA further supports the notion that calpain activation plays an important role in CMV-induced diaphragmatic atrophy and contractile dysfunction.…”
Section: Discussionsupporting
confidence: 92%
“…Other mechanisms of the effects of CS in AE may be related to the prevention of endotoxin-induced secondary liver injury [35], prevention of cytolysis of ballooned hepatocytes by stabilization of the lysosomal membrane [36], and improvement of the functional activity of the remaining hepatocytes [37]. Other studies showed that the preferential increase in the number of HBV-specific CD8 T and CD4 T cells is associated with viral control rather than liver damage [38,39].…”
Section: Discussionmentioning
confidence: 96%
“…Steroids induce an anti-inflammatory effect by providing negative feedback on immunological stimulation, stabilizing cell membrane integrity by inhibition of lysosome peroxidation and through regulation of gene expression pathways [27,28] . Corticosteroids seem to have a positive impact on the extent of IRI in the liver through an anti-apoptotic effect [29–33] .…”
Section: Introductionmentioning
confidence: 99%